Assessment of a regulatory measurement system for the determination of the non-volatile particulate matter emissions from commercial aircraft engines - Kinsey, John S.; Giannelli, Robert; Howard, Robert; Hoffman, Brandon; Frazee, Richard; Aldridge, Michael; Leggett, Cullen; Stevens, Katherine; Kittelson, David; Silvis, William; Stevens, Jeffrey; Lobo, Prem; et al. (Journal of aerosol science, 2021)
The SAE International has published Aerospace Information Report (AIR) 6241 which outlined the design and operation of a standardized measurement system for measuring non-volatile particulate matter (nvPM) mass and number emissions from commercial aircraft engines. Prior to this research, evaluation of this system by various investigators revealed differences in nvPM mass emissions measurement on the order of 15–30% both within a single sampling system and between two systems operating in parallel and measuring nvPM mass emissions from the same source. To investigate this issue, the U. S. Environmental Protection Agency in collaboration with the U. S. Air Force's Arnold Engineering Development Complex initiated the VAriable Response In Aircraft nvPM Testing (VARIAnT) research program to compare nvPM measurements within and between AIR-compliant sampling systems used for measuring combustion aerosols generated both by a 5201 Mini-CAST soot generator and a J85-GE-5 turbojet engine burning multiple fuels. The VARIAnT research program has conducted four test campaigns to date. The first campaign (VARIAnT 1) compared two essentially identical commercial versions of the sampling system while the second campaign (VARIAnT 2) compared a commercial system to the custom-designed Missouri University of Science and Technology's North American Reference System (NARS) built to the same specifications. Comparisons of nvPM particle mass (i.e., black carbon), number, and size were conducted in both campaigns. Additionally, the sensitivity to variation in system operational parameters was evaluated in VARIAnT 1. Results from both campaigns revealed agreement of about 12% between the two sampling systems, irrespective of manufacturer, in all aspects except for black carbon determination. The major source of measurement differences (20–70%) was due to low BC mass measurements made by the Artium Technologies LII-300 as compared to the AVL 483 Micro-Soot Sensor, the Aerodyne Cavity Attenuated Phase Shift (CAPS PMSSA) monitor, and the thermal-optical reference method for elemental carbon (EC) determination, which was used as the BC reference. •Evaluation of multiple fine particle sampling and measurement systems for aircraft turbine engines.•Comparative analysis of black carbon mass measurement instruments to each other and the elemental carbon (EC) reference method.•Black carbon instrument calibration to elemental carbon mass from a propane fueled, laboratory combustion aerosol source.•LII had a lower response (up to 45%) to turbine engine black carbon emissions than photoacoustic and light extinction based instruments and the EC method.